p53-Mediated Oxidative Stress Enhances Indirubin-3'-Monoxime-Induced Apoptosis in HCT116 Colon Cancer Cells by Upregulating Death Receptor 5 and TNF-Related Apoptosis-Inducing Ligand Expression - Matharage Gayani Dilshara; Ilandarage Menu Neelaka Molagoda; Rajapaksha Gedara Prasad Tharanga Jayasooriya; Yung Hyun Choi; Cheol Park; Kyoung Tae Lee; Seungheon Lee; Gi-Young Kim (MDPI AG, 2019)
Indirubin-3′-monoxime (I3M) exhibits anti-proliferative activity in various cancer cells; however, its anti-cancer mechanism remains incompletely elucidated. This study revealed that I3M promotes the expression of death receptor 5 (DR5) and tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) in HCT116 p53+/+ cells, resulting in caspase-mediated apoptosis. However, this study demonstrated that HCT116 p53−/− cells were insensitive to I3M-mediated apoptosis, indicating that I3M-induced apoptosis depends on the p53 status of HCT116 cells. Additionally, in HCT116 p53-/- cells, I3M significantly increased Ras expression, while in HCT116 p53+/+ cells, it reduced Ras expression. Furthermore, I3M remarkably increased the production of reactive oxygen species (ROS), which were reduced in transient p53 knockdown, indicating that I3M-mediated apoptosis was promoted by p53-mediated ROS production. Our results also showed that I3M enhanced transcription factor C/EBP homologous protein (CHOP) expression, resulted in endoplasmic reticulum (ER) stress-mediated DR5 expression, which was upregulated by ROS production in HCT116 p53+/+ cells. Moreover, co-treatment with I3M and TRAIL enhanced DR5 expression, thereby triggering TRAIL-induced apoptosis of HCT116 p53+/+ cells, which was interfered by a DR5-specific blocking chimeric antibody. In summary, I3M potently enhances TRAIL-induced apoptosis by upregulating DR5 expression via p53-mediated ROS production in HCT116 p53+/+ cells. However, HCT116 p53−/− cells were less sensitive to I3M-mediated apoptosis, suggesting that I3M could be a promising anti-cancer candidate against TRAIL-resistant p53+/+ cancer cells. Additionally, this study also revealed that I3M sensitizes colorectal cancer cells such as HT29 and SW480 to TRAIL-mediated apoptosis.